Electrochemical behaviour of (N-R-4-cyanopyridinium)pentaammineruthenium(II) derivatives in acidic medium. Hydrolysis of coordinated nitriles - Naal, Zeki; Tfouni, Elia; Benedetti, Assis Vicente [UNESP] (Elsevier B.V., 1994)
The electrochemical behaviour of N-R-4-cyanopyridinium (4-rcp) (R = methyl, decyl, dodecyl, or benzyl) coordinated to pentaammineruthenium(II) in CF3COOH-CF3COONa (μ = 0.1 M, pH 3) aqueous medium was studied by means of cyclic voltammetry and constant potential electrolysis. The electrochemical oxidation of the metallic centre (Ep ca 0.51 V/SCE) can be described as a reversible monoelectronic charge-transfer followed by an irreversible chemical reaction, which is the hydrolysis of N-R-4-cyanopyridiniumpentaammineruthenium(III) (A) to N-R-4-carboxamidepyridiniumruthenium (III) (B) with the kf1 values depending on the type of alkyl group. The E 1 2 values are not significantly influenced by the nature of the alkyl group. At more negative potential (ca -0.5 V/SCE), B undergoes an electrochemical reduction followed by an aquation reaction to produce aquopentaammineruthenium(II) and free N-R-4-carboxamidepyridinium. The amide was identified by comparison of its cyclic voltammogram and UV-vis spectrum with that of a sample prepared by chemical reaction. The results were also discussed by comparison with other systems, and show that nitrile-amide conversion catalysed by pentaammineruthenium(II) complexes is possible. © 1994.